Efeitos de reservatórios em cascata à montante sobre os padrões espaciais e temporais de diversidade β de ciliados planctônicos em uma planície de inundação neotropical. - Durán, Carolina Leite Guimarães (2019)
In floodplain environments, dam construction can alter connectivity, sediment transport and water discharge in these systems, and cause a process known as biotic homogenization (i.e. reduction in beta diversity). Beta diversity (β diversity) is a fundamental component of biodiversity and changing species composition over time and space is not only a topic of theoretical interest but also has important implications for regional biodiversity planning. Considering this, the possible changes of taxonomic β diversity along a temporal and spatial gradient were investigated in two subsystems of a neotropical floodplain, one of them being impacted by dams and the other free of dams along its course. For the spatial analysis, the results contradict our prediction, so that the Paraná subsystem, strongly impacted by a series of upstream reservoirs, showed no tendency to reduce the β diversity, presenting a pattern similar to that observed for the non-impacted subsystem. In this sense, a process of biotic homogenization was not observed for the community of ciliated protists downstream of the buses. In addition, the turnover component was the most important, showing a high environmental heterogeneity in the studied systems. For the temporal analysis, there was a significant change in species composition from the first to the last year analyzed, only for the subsystem impacted by dams (Paraná), and this increase in β diversity over time was determined mainly by species loss.